Multi-scale design of silicon/carbon composite anode materials for lithium-ion batteries: A review - Yang, Liu; Li, Shuaining; Zhang, Yuming; Feng, Hongbo; Li, Jiangpeng; Zhang, Xinyu; Guan, Huai; Kong, Long; Chen, Zhaohui (Journal of energy chemistry, 2024)
Multi-scale design of silicon/carbon composite anode materials for lithium-ion batteries is summarized on the basis of interface modification, structure construction, and particles size control, aiming at encouraging effective strategies to fabricate well-performing silicon/carbon composite anodes. [Display omitted] Silicon/carbon composites, which integrate the high lithium storage performance of silicon with the exceptional mechanical strength and conductivity of carbon, will replace the traditional graphite electrodes for high-energy lithium-ion batteries. Various strategies have been designed to synthesize silicon/carbon composites for tackling the issues of anode pulverization and poor stability in the anodes, thereby improving the lithium storage ability. The effect of the regulation method at each scale on the final negative electrode performance remains unclear. However, it has not been fully clarified how the regulation methods at each scale influence the final anode performance. This review will categorize the materials structure into three scales: molecular scale, nanoscale, and microscale. First, the review will examine modification methods at the molecular scale, focusing on the interfacial bonding force between silicon and carbon. Next, it will summarize various nanostructures and special shapes in the nanoscale to explore the construction of silicon/carbon composites. Lastly, the review will provide an analysis of microscale control approaches, focusing on the formation of composite particle with micron size and the utilization of micro-Si. This review provides a comprehensive overview of the multi-scale design of silicon/carbon composite anode materials and their optimization strategies to enhance the performance of lithium-ion batteries.